Online purchase intention of personal luxury goods and the mediating role of consumer trust - Ahmad Suki, Amirah; Jan, Muhammad Tahir; Isamudin, Nur Farihah (e-International Publishing House, 2025)
Consumer trust is crucial in online purchase decisions, particularly for luxury goods. The study analyses how brand reputation and online reviews influence consumer trust and the intention to purchase personal luxury goods online. Based on 214 responses from consumers in Malaysia, the study investigates the influence of brand reputation and online reviews on consumer trust and consumers' online purchase intention. The results from PLS-SEM show a significant impact of these factors on consumer trust in online purchases. However, direct effects on purchase intention are not significant. Meanwhile, consumer trust confirms its role as a mediator.